По формуле ( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2 представим в виде многочлена выражение ( x + y - 3 ) ^ 2. Тогда получим: ( x + y - 3 ) ^ 2 = ( ( x + y ) - 3 ) ^ 2 = ( x + y ) ^ 2 - 2 * ( x + y ) * 3 + 3 ^ 2 = ( x + y ) ^ 2 - 6 * ( x + y ) + 9 = x ^ 2 + 2 * x * y + y ^ 2 - 6 * ( x + y ) + 9 = x ^ 2 + 2 * x * y + y ^ 2 - 6 * x - 6 * y + 9 ; В итоге получили, что ( x + y - 3 ) ^ 2 = x ^ 2 + 2 * x * y + y ^ 2 - 6 * x - 6 * y + 9 ; Ответ: ( x + y - 3 ) ^ 2 = x ^ 2 + 2 * x * y + y ^ 2 - 6 * x - 6 * y + 9 .